Noise, Age, and Gender Effects on Speech Intelligibility and Sentence Comprehension for 11- to 13-Year-Old Children in Real Classrooms - Prodi, Nicola; Visentin, Chiara; Borella, Erika; Mammarella, Irene C.; Di Domenico, Alberto (Frontiers in Psychology, 2019)
The present study aimed to investigate the effects of type of noise, age and gender on children’s speech intelligibility and sentence comprehension. The experiment was conducted with 171 children between 11 and 13 years old in ecologically-valid conditions (collective presentation in real, reverberating classrooms). Two standardized tests were used to assess speech intelligibility (SI) and sentence comprehension (SC). The two tasks were presented in three listening conditions: quiet; traffic noise; and classroom noise (non-intelligible noise with the same spectrum and temporal envelope of speech, plus typical classroom sound events). Both task performance accuracy and listening effort were considered in the analyses, the latter tracked by recording the response time using a single-task paradigm. Classroom noise was found to have the worst effect on both tasks (worsening task performance accuracy and slowing response times), due to its spectro-temporal characteristics. A developmental effect was seen in the range of ages (11-13 years), which depended on the task and listening condition. Gender effects were also seen in both tasks, girls being more accurate and quicker to respond in most listening conditions. A significant interaction emerged between type of noise, age and task, indicating that classroom noise had a greater impact on response times for SI than for SC. Overall, these results indicate that, for 11- to 13-year-old children, performance in SI and SC tasks is influenced by aspects relating to both the sound environment and the listener (age, gender). The presence of significant interactions between these factors and the type of task suggests that the acoustic conditions that guarantee optimal SI might not be equally adequate for SC. Our findings have implications for the development of standard requirements for the acoustic design of classrooms.